2016
DOI: 10.4274/tjod.45656
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between estradiol-progesterone alterations after ovulation trigger and treatment success in intrauterine insemination cycles

Abstract: Objective:To assess the relationship between the estrogen-progesterone alterations before and after ovulation trigger and treatment success in intrauterine insemination (IUI) cycles.Materials and Methods:Two hundred fifty-one women with infertility underwent ovulation induction followed by IUI. For all subjects, estradiol and progesterone concentrations were evaluated on the trigger and IUI day. The results were analyzed to assess the relationship between hormone levels and positive pregnancy test.Results:Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Saleh et al (23) also shown that the progesterone level in the HCG injection day is not a predictive factor for pregnancy consequences. Kutlu et al (24) in assessment of patients under IUI treatment showed no difference regarding progesterone level at the time of HCG injection, between cases with or without positive pregnancy.…”
Section: Discussionmentioning
confidence: 92%
“…Saleh et al (23) also shown that the progesterone level in the HCG injection day is not a predictive factor for pregnancy consequences. Kutlu et al (24) in assessment of patients under IUI treatment showed no difference regarding progesterone level at the time of HCG injection, between cases with or without positive pregnancy.…”
Section: Discussionmentioning
confidence: 92%
“…Additionally, compared with the standard regimen, the number of oocytes retrieved and E2 level on hCG trigger day in mild stimulation regimen were significantly decreased. Serum E 2 level reflects the quality of oocytes (19), and it has been shown to promote follicle production, upregulate gonadotropin receptors expression, repress the apoptosis of granulosa cell, and the number of dominant follicles is positively correlated with E 2 levels (20). A previous study also showed that the mild stimulation regimen (CC/LE in combination with Gn) reduced E 2 level on hCG trigger day and decreased the number of mature oocytes when compared with the standard regimen, thereby decreasing the chance of receiving live frozen embryos (21).…”
Section: Discussionmentioning
confidence: 99%
“…The comparison revealed significantly increased levels of progesterone after trigger in both groups; however, although there were estradiol level drops in both groups, the drop in the group with negative pregnancy tests was statistically significant. Significant drops in estradiol concentrations after ovulation trigger are associated with IUI cycle treatment failure [44].…”
Section: Recent Advancesmentioning
confidence: 99%